What If Low Back Pain Is the Most Prevalent Parkinsonism in the World? - Jacobs, Jesse V.; Henry, Sharon M.; Horak, Fay B. (Frontiers in Neurology, 2018)
Low back pain (LBP) has a point prevalence of nearly 10% and ranks highest in global disease burden for years lived with disability; Parkinson's disease (PD) ranks in the top 100 most disabling health conditions for years lost and years lived with disability [Stovner et al. Acta Neurol Scand Suppl. 2014;198:1-6]. Recent evidence suggests that people with chronic, recurrent LBP exhibit many postural impairments reminiscent of a neurological postural disorder such as PD. We compare and contrast postural impairments associated with LBP and PD in order to inform treatment strategies for both conditions. The literature suggests both LBP and PD associate with impaired proprioceptive function, sensory orientation during standing balance, anticipatory postural adjustments, automatic postural responses, and striatal-cortical function. Although postural impairments are similar in nature for LBP and PD, the postural impairments with LBP appear more specific to the trunk than for PD. Likewise, although both health conditions associate with altered striatal-cortical function, the nature of the altered neural structure or function differ for PD and LBP. Due to the high prevalence of LBP associated with PD, focused treatment of LBP in people with PD may render benefit to their postural impairments and disabilities. In addition, LBP would likely benefit from being considered more than just a musculoskeletal injury; as such, clinicians should consider including approaches that address impairments of postural motor control.